Cyberbullying Dan Pertanggungjawaban Hukum Pidana Di Era Digital - Alif Sultan; Muhammad Fahmi Reza; Asmak Ul Hosnah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Cyberbullying, a form of digital violence, has significant psychological and social effects due to advancements in information and communication technology. Victims of cyberbullying may experience psychological pressure, as well as loss of social relationships and reputation. The aim of this study is to examine how perpetrators of cyberbullying in Indonesia are held criminally accountable, with particular emphasis on the application of the Information and Electronic Transactions Law (UU ITE), the Indonesian Criminal Code (KUHP), and the Child Protection Law. This study employs a qualitative normative juridical approach, analyzing legal documents, academic research, and relevant court decisions. The results indicate that, although a legal framework exists and has been implemented, several challenges hinder its enforcement. These challenges include easily deletable digital evidence, difficulties in identifying perpetrators, and low public awareness. To protect victims of cyberbullying, this study recommends improving digital literacy, strengthening reporting systems, and enforcing laws consistently.